2007
DOI: 10.1590/s1678-91992007000100010
|View full text |Cite
|
Sign up to set email alerts
|

Uveitis following anti-snake venom therapy

Abstract: Snakebite is a common medical emergency in the tropics, causing multisystemic involvement. Ophthalmic manifestations after snakebite have included ptosis and ophthalmoplegia. Uveitis as an immunological complication following therapy with anti-snake venom (ASV) serum has been rarely reported in literature.We reported two patients who developed uveitis and acute renal failure following snakebite treatment with ASV serum. Both patients recovered uneventfully with appropriate therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 1 publication
1
10
1
Order By: Relevance
“…The response to systemic steroids also favours an immune response as the pathogenic mechanism for this uveitis. 20 In present study, the fibrinoid anterior uveitis , hypotony and vitritis developed within 4 days unlike in S Nayak et al…”
Section: Discussioncontrasting
confidence: 48%
“…The response to systemic steroids also favours an immune response as the pathogenic mechanism for this uveitis. 20 In present study, the fibrinoid anterior uveitis , hypotony and vitritis developed within 4 days unlike in S Nayak et al…”
Section: Discussioncontrasting
confidence: 48%
“…Late onset uveitis following venomous bite is probably due to serum sickness like response to horse ASV serum. 14 In the present study common ocular manifestations of neurotoxic snake bites were ptosis followed by diplopia, ophthalmoplegia and optic neuritis, in order of decreasing incidence. Seneviratne U et al 15 in their study of 56 patients with neurological manifestations of snake bite, reported that ptosis and ophthalmoplegia were the commonest neurological manifestations Singh J et al, 3 in an analysis of 33 venomous snake bites in a military operational area of north India reported 21 patients to be neurotoxic in nature.…”
Section: Discussionsupporting
confidence: 47%
“…Snake bite related ocular complications have been rarely reported in the literature, the common problem described after snakebite is in the form of ophthalmoplegia 6 . Other ocular manifestations as effects of snakebite reported as keratomalacia, macular infarction, including haemorrhages into the conjunctiva, anterior chamber, lid oedema, conjunctival chemosis, retinal and optic nerve oedema, optic neuritis, and optic atrophy, globe necrosis and visual loss due to cortical infarction, uveitis and endophthalmitis [7][8][9][10] . In this case, vision loss is due to bilateral retinal haemorrhage and cotton wool spot subsequent to the snakebite.…”
Section: Discussionmentioning
confidence: 99%